Dos contornos do corpo às formas do eu: a construção de subjetividades femininas na revista Sou+Eu! - Cruz, Patrícia Monteiro (2010)
The current study aimed to understand how the media operates the construction of feminine subjectivity, constituting forms of self-projection by modeling the body and appearance. According these objectives, it had the body of 12 cover stories of the women's magazine "Sou+Eu!", of Editora Abril, reported between July 2008 to June 2009. Using reports sent by readers - that start to work as collaborators - and placed an order of the media discourse, the publication focuses on success stories about weight loss practices, associating them to a discourser of overcoming and self-esteem linked to ideal body image. The study analyzed how the diets discourse regiment woman around an aesthetic pattern on the thin body, and thus, as the magazine "Sou+Eu!" built knowledge about the female, reinforcing the place of media in current production of subjectivities. The approach of this research was the sociology of everyday life and the method of procedure was the analysis of media discourse and its implications for female subjectivity. Evidencing the social forms, the study of everyday life becomes effective to insinuate (instead of conceptualizing) and demonstrate (rather than explain) the complexities and subtleties of journalism and its influence on contemporary society, in which appearance and visibility are based on the tonic of daily living. Key-words: Media. Everyday life. Feminine subjectivity. Discourse. Magazine.